Spatial Analysis and Risk Factor Association of Pneumonia Cases Among Under-Five Children in Surakarta City - Septiana, Della Hani; Santoso, Dian Budi (International Journal of Health and Information System, 2025)
The increasing number of pneumonia cases among under-five children in Surakarta City over the past three years indicates the need for preventive measures to curb the rise. Spatial analysis and risk factor assessment are essential tools for understanding the geographical distribution and contributing determinants of pneumonia in young children.; (1) Background: To analyze the spatial distribution and associations between risk factors and pneumonia cases among under-five children in Surakarta City.; (2) Methods: This research is a quantitative study with a cross-sectional design; (3) Results: Multivariate regression showed that poor nutrition, population density, rainfall, and humidity significantly influenced pneumonia prevalence.; (4) Conclusions: The prevalence of pneumonia in toddlers shows a high level of vulnerability in Sangkrah subdistrict. The Health Office of Surakarta City can intervene with priority level 1 area.